The Relationship Between Mothers’ Digital Health Literacy and the Utilization of Social Media as a Source of Child Health Information - Rubiyanta rubiyanta; Hakim Anasulfalah; Tri Yuniarti; Ahmad Syauqi Mubarok; Joko Tri Atmojo; Aris Widiyanto; Hendra Dwi Kurniawan (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2026)
The development of social media has transformed mothers’ behavior in accessing child health information. The increasing use of social media as a health information source highlights the importance of digital health literacy in evaluating the credibility and quality of digital health information. This study aimed to analyze the relationship between mothers’ digital health literacy and the utilization of social media as a source of child health information. This study employed a Systematic Literature Review (SLR) method following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Article searches were conducted through Scopus, PubMed, ScienceDirect, Google Scholar, and SpringerLink using keywords related to digital health literacy, social media, mothers, and child health information. The reviewed articles were published between 2020 and 2025 and selected based on inclusion and exclusion criteria according to the PICO framework. A total of 10 articles meeting the eligibility criteria were analyzed using thematic synthesis techniques. The findings indicated that mothers with higher levels of digital health literacy were more capable of evaluating the credibility of health information, comparing multiple information sources, and critically utilizing social media for child healthcare decision-making. In contrast, lower digital health literacy increased the risk of exposure to health misinformation on social media. This study concludes that digital health literacy has an important relationship with the utilization of social media as a source of child health information. The findings provide important implications for developing digital health literacy education programs to support safer and evidence-based use of social media in child healthcare.